Kajian Keuletan pada Beton Variasi Limbah Granit Sebagai Substitusi Parsial Agregat Kasar - Farhan Nuraziz; Wibowo Wibowo; Endah Safitri (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Concrete is one of the most common construction materials used throughout the world. Concrete consists of three main components: cement, coarse aggregate, and fine aggregate. Coarse aggregate serves as the main structural component in concrete, providing strength and resistance to external loads. Currently, technological advancements in construction are rapidly progressing. Therefore, innovation in concrete production is necessary, one of which is recycled aggregate concrete. The aim of this research is to determine the effect of using granite waste as a partial substitute for coarse aggregate on toughness of concrete. The method used in this research is experimental method. In this study, the variation level of granite waste used in this study was 0%; 15% ; 30% ; and 45%. The objects used for this research are blocks with dimensions of 400x100x100 mm tested using a Universal Testing Machine. The results of this research show that the toughness value obtained from the results of toughness testing on concrete with varying levels of 0% granite waste; 15% ; 30% ; and 45% respectively, namely 1.9589 kNmm; 2.2362 kNmm; 2.4189 kNmm; and 2.2118 kNmm.